Hemophagocytic lymphohistiocytosis, a rare condition in renal transplant - a case report - Lima,Valentine de A. C. de Castro (2018)
Abstract Hemophagocytic lymphohistiocytosis (HLH) is an uncommon and life-threating condition characterized by major immune activation and massive cytokine production by mononuclear inflammatory cells, due to defects in cytotoxic lymphocyte function. It is even more unusual in renal transplant recipients, in which it is often associated with uncontrolled infection. The mortality is high in HLH and differential diagnosis with sepsis is a challenge. The approach and management depend on the underlying trigger and comorbidities. We report a case of a 50-year-old renal transplant female admitted with fever and malaise 3 months post-transplant and presenting anemia, fever, hypertriglyceridemia, high levels of serum ferritin, and positive CMV antigenemia. Urine was positive for decoy cells and BKV-DNA. Graft biopsy showed CMV nephritis. Both blood and urine cultures where positive for E. coli. Hemophagocytosis was confirmed by bone marrow aspiration. Immunosuppression was reduced, and the patient received high-dose intravenous immunoglobulin and dexamethasone, with complete response after 3 weeks. We highlight the importance of early diagnosis and proper management of a rare and serious condition in a renal transplant patient, which can allow a favorable clinical course and improve survival rate.